Final freedom : - Vorenberg, Michael (Cambridge University Press, 2001)
This innovative, well-written work focuses on the emancipation of American slaves subsequent to the Emancipation Proclamation and leading up to the passage of the Thirteenth Amendment, which constitutionalized the issue of slavery. Although Vorenberg (Brown Univ.) acknowledges the depth and breadth of scholarship addressing the progress of African Americans after the Civil War, he asserts that comparatively scant attention has been paid to the process by which emancipation was legalized. Personalities, famous and not so well known, on both sides of the emancipation issue are heard